Kajian Kawasan Pergudangan di Kabupaten Penajam Paser Utara - Dimaz Harits; Surahman Surahman; Afif Bizrie Mardhanie; Thomas Robert Hutauruk; M. Salmani; Mohammad Faisal (Abdimas Universal, 2022)
Penajam Paser Utara Regency is one of the regencies in East Kalimantan that is predicted to be a candidate for the new capital city of the Unitary State of the Republic of Indonesia. Industrial development has changed along with the increasing intensity of development implementation. The designation of the Buluminung Industrial area has been determined, to support its existence, the Penajam Paser Utara Regency Government plans to build a warehousing area. This article briefly reviews the results of spatial analysis, transportation analysis, technical analysis, supply chain management analysis, financial economic analysis, social analysis, environmental risk analysis. The results of this study are expected to provide an overview of the prospects for the development of warehousing areas in Penajam Paser Utara Regency and can be utilized as well as possible by Penajam Paser Utara Regency.